Essays on corporate finance - YUN, Su Hee (Institutional Knowledge at Singapore Management University, 2024)
Chapter 1. The impact of ESG disasters on Green and Brown firms I investigate the effect of a firm’s prior ESG reputation on the market impact of ESG incidents. I find that firms with a better ESG reputation, i.e., higher ESG ratings, experience less negative stock-market reactions and analysts' forecast revisions compared to firms with a poorer ESG reputation. But managers of Greener firms, when producing earnings guidance, do not forecast a lower impact of these incidents on future earnings. Similarly, actual decreases in future earnings following these incidents are not significantly different between Green and Brown firms. Altogether, the evidence suggests that investors and analysts underreact to ESG incidents if the firms affected by these incidents have a stronger prior ESG reputation. Chapter 2. Fraud Risk and Corporate Performance I examine the impact of ex ante fraud risk on a firm's stock market performance and how firms respond to this risk. Using a detection-controlled estimation framework and new instrumental variables, I estimate the ex ante probabilities of a firm (1) committing fraud and (2) being detected for fraud. I find that firms with a high fraud detection probability have low returns, which is consistent with the large negative stock returns observed upon the revelation of fraud. In contrast, firms with a high probability of committing fraud have higher returns, which is consistent with the view that fraudulent firms are riskier on average. Additionally, firms with a high probability of committing fraud are observed to hold less cash, invest less, and increase payouts, while those with a high probability of detection tend to hold more cash.